Individuals with larger head volume have better learning ability in wild chestnut thrushes. (2nd June 2022) - Lou, Yingqiang; Zou, Yuqi; Fang, Yun; Swenson, Jon E; Pape Møller, Anders; Sun, Yuehua
Abstract: Recent comparative studies on fish and mammals have suggested that brain size is associated with cognitive ability, such as problem solving and self-control; larger-brained individuals are assumed to have better cognitive ability. However, it remains largely unexplored whether larger-brained birds perform better in learning and spatial memory tests. Here, we used two experiments (novel skill learning task and spatial memory task) to examine whether head volume (proxy for brain size) could predict the learning performance and spatial performance in wild chestnut thrushes ( Turdus rubrocanus ). First, we found that chestnut thrushes with larger head volume were more likely to learn the novel skill than individuals with smaller head volume. Second, individuals with larger head volume relative to their tarsus (relative head volume) learned the novel skill faster. Age, sex, and exploratory tendency of individuals were not related to learning performance or learning speed. Finally, head volume, relative head volume and age was not associated with spatial performance in the spatial memory tasks. Together, these findings provided empirical evidences for the relationship between head volume and the ability of novel skill learning, and also provide a non-invasive method for studying the relationship between cognitive ability and head volume in other bird species. Abstract : Previous studies have reported a relationship between brain size and cognitive ability in several species. In this study, we found that adult chestnut thrushes were less exploratory than juveniles. Chestnut thrushes with a larger head volume were more likely to learn a novel skill than individuals with a smaller head volume. Furthermore, individuals with a larger head volume relative to their tarsus length learned the novel skill more quickly.